Determination of the financial minimum in a municipal budget to deal with crisis situations - Kudlák, Aleš; Urban, Rudolf; Hošková-Mayerová, Šárka (Springer New York, 2020)
This paper offers an analysis of the mission and role of municipalities in the Czech national crisis management system. The paper clarifies the nature of population protection within the national security system accentuating resource availability. The significance of local municipal budgets as the baseline to crisis solution support within the administered area is discussed. The problem is not the system of budgets or the budgeting system itself at the level of local government. The key issue, however, is the determination of budget resources, which are primarily predetermined ex ante for the crisis prevention resolution phase. Current legislation does not address this requirement. The authors also point out the fundamental influence of local policy in the allocation of resources in the municipal budget in relation to their political preferences. Therefore, the authors of the article propose the calculation method for the standard minimum amount of financial resources allocated to coping with crises in the municipal budget at their level, as appropriate. The submitted proposal will contribute to guaranteeing a minimum level of preparedness for crisis management in ensuring the safety of all residents.
Stanovení finančního minima v rozpočtu obce k řešení krizových situací
Keywords: crisis management; population protection; resource allocation for crisis situations; municipal budget; krizový management; ochrana obyvatelstva; alokace zdrojů pro krizové situace; municipální rozpočet